1991
DOI: 10.1002/bjs.1800780807
|View full text |Cite
|
Sign up to set email alerts
|

Tropic role of enteroglucagon in pancreatic adaptation to subtotal enterectomy

Abstract: Proximal small bowel resection causes pancreatic hyperplasia, presumably via a humoral mechanism. Although cholecystokinin can stimulate pancreatic growth, its proximal distribution in the gut makes it an unlikely intermediary after proximal small bowel resection. The potential roles of neurotensin and enteroglucagon were studied, since these hormones are mainly secreted from the ileum and proximal colon. Male Wistar rats (n = 50) weighing 200-250 g were randomized to receive 90 per cent proximal small bowel r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1993
1993
1998
1998

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…It has also been reported that enteroglucagon plays a major role in the adaptive response of the residual ileum after a small bowel resection [5,6]. Furthermore, Watanapa et al reported that enteroglucagon may have a pancreatotrophic, in addition to enterotrophic, activity [16]. We also reported that enteroglucagon plays an important role in the adaptive pancreatic hyperplasia observed after a 90% proximal small bowel resection [17,18].…”
Section: Discussionsupporting
confidence: 62%
“…It has also been reported that enteroglucagon plays a major role in the adaptive response of the residual ileum after a small bowel resection [5,6]. Furthermore, Watanapa et al reported that enteroglucagon may have a pancreatotrophic, in addition to enterotrophic, activity [16]. We also reported that enteroglucagon plays an important role in the adaptive pancreatic hyperplasia observed after a 90% proximal small bowel resection [17,18].…”
Section: Discussionsupporting
confidence: 62%
“…Both 1 week and 1 month after 90% proximal small bowel resection, 5-72% increments in pancreatic mass correlated with 83-150% increments in enteroglucagon levels, while neurotensin levels were unchanged (Watanapa et al, 1991a). CCK proved to be another candidate for the role of pancreatotropin.…”
Section: Other Specific Dietary Constituentsmentioning
confidence: 90%
“…but lowers pancreatic polypeptide [40]. After ileocecal resection, pancreatic hyperplasia has been shown without changes in basal levels of plasma CCK [41], whereas after subtotal enterectomy increased basal CCK and enteroglucagon levels accompanied the pancreatic growth [42,43]. Thus, gastrointestinal surgery evokes different hormonal effects, that probably result in the different pancreatic changes seen.…”
Section: Discussionmentioning
confidence: 99%